2018
DOI: 10.1061/(asce)hy.1943-7900.0001422
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Organic Combined Sewer Sediment Release and Transport

Abstract: Accurate predictions of sediment loads released by sewer overflow discharges are important for being able to provide protection to 7 vulnerable receiving waters. These predictions are sensitive to the estimated sediment characteristics and on the site conditions of in-pipe 8 deposit formation. Their application without a detailed analysis and understanding of the initial conditions under which in-sewer deposits 9were formed normally results in very poor estimations. In this study, in-sewer sediment samples dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous studies highlighted CSO pollution and its adverse impacts on the health of the receiving water bodies (Hvitved-Jacobsen 1982; Phillips et al 2012;Rechenburg et al 2006), as well as indicated remarkable contribution of sewer sediments to quality of CSOs (Chebbo et al, 1995;Gromaire et al, 2001;Ashley et al, 2004;Gasperi et al, 2010). The accumulation of these in-sewer deposits also causes more frequent CSOs due to reduction in conveyance e ciency of the sewer network (Crabtree 1989;Seco 2014;Veliskova & Sokac 2019). Therefore, sewer sediments can act as a sink-source of pollutants that contribute to rising pollution level in wet weather ows and receiving water bodies.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies highlighted CSO pollution and its adverse impacts on the health of the receiving water bodies (Hvitved-Jacobsen 1982; Phillips et al 2012;Rechenburg et al 2006), as well as indicated remarkable contribution of sewer sediments to quality of CSOs (Chebbo et al, 1995;Gromaire et al, 2001;Ashley et al, 2004;Gasperi et al, 2010). The accumulation of these in-sewer deposits also causes more frequent CSOs due to reduction in conveyance e ciency of the sewer network (Crabtree 1989;Seco 2014;Veliskova & Sokac 2019). Therefore, sewer sediments can act as a sink-source of pollutants that contribute to rising pollution level in wet weather ows and receiving water bodies.…”
Section: Introductionmentioning
confidence: 97%
“…Sewer sediments also mount wherever water ow decelerates, for instance, abrupt changes in shape or dimension of pipes, divergent or low slope sectors, etc. Thus, the accumulation of sewer sediments are temporal and spatial dependent, directly linked to water velocity inside sewer network (Seco 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the models do not satisfactorily simulate sediment depths or the subsequent accumulation, erosion and transport processes in sewer systems. 4,5 Poorly predictive sediment models stress the need for an improved technique to monitor sediment accumulation in sewer systems by developing a robust evidence base and establishing a proactive data-driven sewer maintenance regime. Monitoring in-pipe sediment properties and accumulation behaviours could offer valuable insights into sediment transport dynamics and performance.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sediment has been established to be found even in sewerage pipes, commonly described as 'in-sewer sediment' (Crabtree, 1989;Tait et al, 1998;Seco et al, 2018). When the flow velocity is considerably lower than the critical velocity, the sediment tends to be deposited and, overtime, accumulated to a certain depth.…”
Section: Introductionmentioning
confidence: 99%